Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Par où attaquer le « partage inégal » du « travail ménager » ? - Delphy, Christine (Nouvelles Questions Féministes, 2003)
Le travail domestique a été beaucoup étudié par les féministes depuis trente ans. Mais ce qu’il désigne : la prise en charge de tout le travail non payé de la maison par les femmes, n’a pas changé. Le « non-partage » est dénoncé, mais peu de solutions concrètes sont proposées. Le caractère « privé » a été dénoncé en ce qui concerne les violences contre les femmes, mais pas l’appropriation de leur travail. La théorie matérialiste qui fait de cette appropriation l’un des socles du patriarcat est rappelée ; le rôle de l’État est examiné, et la conclusion est que nos sociétés, via le marché du travail, mais aussi via le système fiscal et de sécurité sociale, contribuent à rendre possible cette appropriation du travail des femmes et des concubines par les hommes. On suggère d’adopter comme revendication : la suppression des subventions d’État aux ménages où la femme ne travaille pas, en même temps que l’application du droit commun au travail domestique, c’est-à-dire le paiement par le bénéficiaire. L’hypothèse est que les hommes seront plus enclins à faire leur part quand ne pas la faire leur reviendra très cher.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discipline; europe; france; féminisme marxiste; féminisme matérialiste; histoire et politique; inégalités; marxisme; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique